ANALYSIS OF BRONZE AND IRON AGES (YAZ CULTURE) SETTLEMENTS IN GOLBAHAR DISTRICT OF CHENARAN COUNTY: A LANDSCAPE ARCHAEOLOGY APPROACH - Mohammad Hossein REZAEI (Journal of Ancient History and Archaeology)
Landscape archaeology is a multidisciplinary field that examines the relationship between humans and their environment throughout history. The Golbahar Plain is one of the widest intermountain plains in the northeastern region of Iran. Surveys and documentation of the Golbahar District of Chenaran County were done with the aim of identifying, registering, and compiling the chronology of ancient sites, as well as determining the role of environmental resources in the formation process of sites in this area. After identifying the sites, samples were collected systematically; the area of the sites was divided into 10-by-10-meter grids, and the samples were collected. After conducting a field survey and specifying the chronology of pottery, the settlement patterns in the studied landscape were analyzed using a GIS system. The most important results of the present study are the identification and discovery of 58 ancient sites from the Bronze Age to the Islamic period. In the present study, the settlement pattern of the identified sites that were related to the Bronze and Iron Ages has been investigated and analyzed. The findings indicate that in this particular environmental context, variables such as proximity to the river and altitude have played a crucial role in the formation of settlements on this plain. According to the relative chronology of the sites, it can be stated that most sites of Golbahar Plain have been inhabited from the beginning of Yaz I, and only in CHS-9 and CHS-22 sites, did habitation continue in them until Yaz III.